A survey on the prevalence and risk indicators of dental erosion among 18-22 years old students of Diyala university - Salman, Eman D.; Qasim, Aisha A. (Edelweiss Applied Science and Technology, 2024)
The aims of the study were to investigate prevalence and severity of dental erosion, and its related etiological risk factors and habits among students of university of Diyala. A cross-sectional survey of 404 university of Diyala undergraduate students, ages 18 to 22, was carried out. The participants were split into four groups: First Academic Stage (96), Second Academic Stage (133), Third Academic Stage (91), and Fourth Academic Stage (84). Before the exam began, general information and questions were captured in a unique form designed for data recording. Students also signed an informed permission form indicating their willingness to participate in research before the exam began. The prevalence and severity of dental erosion were classified for each tooth using the basic erosive wear examination (BEWE). The erosive wear criterion for each surface, tooth, and sexton ranges from 0 to 3. In this recent study females were higher percentage of dental erosion 56.9% than males 43.1% in score 0 of BEWE, also females were higher percentage of dental erosion in score 1, score 2 and score 3. Age 18 has a larger percentage of erosion (7.8%) in score 1 and no erosion in score 3, however age 19 has the highest score (18.2%) compared to the other age groups. Higher percentages in score 2 were 28.4% and 33.3%, respectively, for those aged 20 and 21. The percentage of degradation was higher in score 1 42.7% at age 22. Severe erosion was found in females than males, the enamel layer appears to be more impacted by tooth erosion as indicated by scores 1 and 2, which were determined by the BEWE index.